Th1/Th2 cytokine polarization in milk according to different pathogens causing subclinical mastitis in cows - Safak, Tarik; Risvanli, Ali; Asci-Toraman, Zulal (Croatian Dairy Union, 2022)
The aim of this study to determine the Th1/Th2 cytokine balance in milk according to the bacterial species that cause subclinical mastitis in cows. The California Mastitis Test (CMT) was applied to the selected cows. The cows were divided into four groups: cows with negative CMT (n = 45); Escherichia coli (E. coli) group included only cows with E. coli growing in CMT-positive milk samples (n = 45); Streptococcus agalactiae (S. agalactiae) group included cows with only S. agalactiae growing in CMT-positive milk samples (n = 45); Staphylococcus aureus (S. aureus) group included cows with only S. aureus growing in CMT-positive milk samples (n = 45). Somatic cell count (SCC) in fresh milk samples was measured using the DeLaval Cell Counter device. Also, cytokine analyses were performed using Species-specific commercial ELISA kits. Tumor necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma) concentrations were relatively high in the E. coli group, but the interleukin (IL)-2 concentration was low. The lowest concentration of IL-4 was found in the CMT-negative group. The highest IL-5 concentration was found in the S. agalactiae group, while the highest milk IL-10 concentration was found in the S. aureus group. Also, T helper (Th1/Th2) polarization shifted towards Th1 in milk with mastitis caused by E. coli. Th1/Th2 polarization was shifted to Th2 in milk with mastitis caused by S. aureus and S. agalactiae. Based on our findings, cellular immunity should be maintained in mastitis cases due to E. coli, and humoral immunity should be supported in mastitis caused by S. aureus and S. agalactiae.
Polarizacija citokina Th1 / Th2 u mlijeku u odnosu na patogene uzro?nike subklini?kog mastitisa kod krava
Keywords: Th1/Th2 cytokine; subclinical mastitis; cow; California Mastitis Test